(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Glucose is a cheap and readily available substrate for production of large-scale chemicals. Synthesis of xylitol, a high demand chemical in global market is currently done by using xylose, which contributes to its high operational cost. Studies on production of xylitol from glucose have explored several approaches, from sequential fermentation to multiple and single gene expression. Xylitol-5-phosphate dehydrogenase (XPDH), is an enzyme that enables conversion of glucose to xylitol in a single step fermentation. This study explores conversion of xylitol from glucose in E. coli by the expression of xpdh from Clostridium difficile with modifications in metabolic pathways to enhance xylitol production. The xpdh gene was carried by pACYC-Duet-1 expression vector and induced by the addition of IPTG. Initial screening of E. coli expressing xpdh (NA116) was done by shake-flask fermentation for 24 hours and its metabolites were analyzed by HPLC. NA116 was able to produce 0.273 g/L xylitol from 4.33 g/L consumed glucose in 24 hours. Further metabolic pathway modification to eliminate competing pathways yielded four mutants, NA207 (∆rpiA), NA208 (∆rpiB), NA209 (∆pgi) and NA211 (∆rpi∆Apgi). Screening of mutants for xylitol production showed that highest xylitol production from glucose was achieved by NA211 with almost double the amount of the original strain, 0.585 g/L. This showed successful xylitol conversion from glucose in a single fermentation in E. coli with improved yield through metabolic pathway modification.